Unexpected Michael Additions on the Way to 2.3, 8.9‐Dibenzanthanthrenes with Interesting Structural Properties. Issue 27 (3rd June 2016) - Reus, Christian; Lechner, Marc P.; Schulze, Matthias; Lungerich, Dominik; Diner, Colin; Gruber, Marco; Stryker, Jeffrey M.; Hampel, Frank; Jux, Norbert; Tykwinski, Rik R.
Abstract: The synthesis and properties of a new polycyclic aromatic hydrocarbon containing eight annulated rings and based on the anthanthrene core is described. An unexpected, nucleophile‐dependent Michael addition to a dibenzanthanthrene‐1, 7‐dione is found, giving a product with three triisopropylsilylacetylene units and a remarkable solid‐state structure (as determined by X‐ray crystallography). Abstract : Eight is enough : A new polycyclic aromatic hydrocarbon containing eight annulated rings and based on the anthanthrene core is synthesized. The dibenzanthanthrene‐1, 7‐dione reacts unexpectedly with aryl and acetylenyl lithium via Michael addition (see scheme).